2019
DOI: 10.3389/fmicb.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactate on the Microbial Community and Process Performance of an EBPR System

Abstract: Candidatus Accumulibacter phosphatis is in general presented as the dominant organism responsible for the biological removal of phosphorus in activated sludge wastewater treatment plants. Lab-scale enhanced biological phosphorus removal (EBPR) studies, usually use acetate as carbon source. However, the complexity of the carbon sources present in wastewater could allow other potential poly-phosphate accumulating organism (PAOs), such as putative fermentative PAOs (e.g., Tetrasphaera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…It should be also noted that the relative abundances obtained from 16S rRNA gene sequences do not necessarily correspond to the actual population abundance due to PCR biases, variation in the number of 16S rRNA gene copies across different organisms, the presence of legacy DNA from EPS, nonactive organisms, etc. Therefore, the relative abundance of organisms revealed by 16S rRNA gene sequencing cannot be directly compared with FISH results that detect active populations and use biomass volume as a metric (Rubio‐Rincón et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be also noted that the relative abundances obtained from 16S rRNA gene sequences do not necessarily correspond to the actual population abundance due to PCR biases, variation in the number of 16S rRNA gene copies across different organisms, the presence of legacy DNA from EPS, nonactive organisms, etc. Therefore, the relative abundance of organisms revealed by 16S rRNA gene sequencing cannot be directly compared with FISH results that detect active populations and use biomass volume as a metric (Rubio‐Rincón et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of fermentative PAOs such as Tetrasphaera could also prove to be detrimental to the EBPR process since an additional source of energy (as ATP) such as the one provided via fermentation could cease the poly-P hydrolysis. This theory is supported by Marques et al (2017) and Rubio-Rincón et al (2019). The latter suggested that neither Tetrasphaera nor Ca.…”
Section: Introductionmentioning
confidence: 86%
“…The reactor's working capacity was 2.5 L, with an internal diameter of 12.5 cm and a water depth of 20.5 cm. The overall experimental setup is comparable to the one used by Rubio-Rincón et al (2019).…”
Section: Sbr Operationmentioning
confidence: 99%
“…This amount of biomass is assessed by FISH where a quantification is made based on cell-surface area. Recently in other studies a similar discrepancy between biovolume and cell numbers due to differences in cell size have been reported (Saccà 2016;Domaizon et al 2017;Rubio-Rincón et al 2019) A "full cycle rRNA analysis" of a microbial community structure, as proposed by Amann, Ludwig and Schleifer (1995) is needed to get a quantitative view of a microbial community structure.…”
Section: Microbial Community Analysis Showed a Difference In Biomass Quantification Between Fish And 16s-based Methodologiesmentioning
confidence: 65%